CREATING A CONTINENTAL AGENDA FOR - Narrandes, Roshnee (My University, 2011)
One of the key objectives of the African Union (AU) is to promote and ensure continental integration. For the AU to be an engine of continental integration it needs a popular constituency at a national level. Currently such a national constituency does not exist as the AU policy and decision-making is a project of the Office of the President and/or sections of the Ministries of Foreign Affairs. The purpose of this research is to explore and document the challenges, constraints and opportunities that civil society in Africa experiences in actively engaging the African Union, so as to assume the space of a popular constituency. A qualitative methodology of research was used where five key Africans who work with, or on, the African Union were interviewed. The main finding of the research is that the African Union is still a long way from being a people-driven process. While efforts are being made by both civil society and the African Union to ensure the inclusivity of the voices of ordinary Africans in continental processes, the failure at state level to provide structures and mechanisms to do so makes the process of collective continental integration most unlikely. Before an appropriate national model for integration can be established, adopted and utilised, the African Union needs to ensure the inclusion of the voices of the people of Africa into continental process by putting in place structures and mechanisms at state level that will create a truly people-driven process
MM - P&DM
Keywords: African Union; Civil society